Models and Methods for Operations in Port Container Terminals - Gudelj, Anita; Krčum, Maja; Twrdy, Elen (Promet - Traffic&Transportation, 2012)
The management of a container terminal is a complex process that involves many decisions. Among the problems to be solved, there are the spatial allocation of containers on the terminal yard, allocation of ships to berths and cranes, scheduling priorities and operations in order to maximize performances based on some economic indicators. Since the container port facilities are very expensive, it is desirable to optimize their performance, making better management decisions. This paper wants to present the contribution of the simulation and optimization techniques with the aim of improving the cooperation between different types of equipments, increasing the productivity of the terminal and helping in minimizing costs. In particular, the Petri net is used to present berth operations, and the genetic algorithm is used for scheduling container loading/unloading operations by cranes in order to minimize the maximum time it takes to serve a given set of vessels.KEYWORDS: transportation, berth management, scheduling, simulation, optimization